« Sea, sex and sun » : la sexualité dans la mythologie du surf way of life - Adolphe Maillot (Genre, Sexualité et Société)
The “Surf way of life”, a lifestyle based on sensual pleasures, is often presented as “liberating”. Born in the fifties on californian beaches, surf riding is, rather than a sport, a “philosophy” or a “way of life” according to passionate surfers. There is a real mythology around this sport. Individuals feel better and more important through the waves and the narrations of magnification made by specialized magazines or publicity. The main hero of this mythology is the “soul surfer”, whose exceptional sexual vitality is not the least of his qualities. This article will put into perspective the liberating aspect of a sports-based and hedonistic ideology, emphasizing in particular the domination of the heterosexual pattern.